Perancangan dan Implementasi Sistem Elektrik serta Otomasi pada Mesin Pencetak Briket Berbasis Cangkang Kelapa Sawit dengan Kapasitas 40 Kg/jam - Sandi, Aris; Yunaidi, Yunaidi; Laksono, Vengky Adi; Christiyadi, Vito Savero (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2025)
Palm oil is a leading agricultural commodity in Indonesia, producing CPO and PKO from the processing of fresh fruit bunches. As palm oil production increases, the volume of solid waste also increases. Solid waste from this industry, such as empty fruit bunches, shells, and fibers, contains high levels of organic matter that can pollute the environment if not managed properly. Briquettes are an alternative energy source that can be produced from this waste. This research aims to utilize palm oil shell waste into high-quality briquettes by developing an efficient charcoal briquette-making machine. The focus of the research is on developing a semi-automatic machine using a pneumatic system and a three-phase motor. Theoretical screw speed was approximately 44 rpm, while direct measurement on the machine showed 43 rpm. Furthermore, the theoretical results obtained a motor power requirement of 667.3 Watts.